All post-translational modifications except propeptide cleavage are required for optimal secretion of coagulation factor VII - Bolt, Gert; Steenstrup, Thomas D.; Kristensen, Claus (Thrombosis and Haemostasis, 2007)
Human coagulation factor VII (FVII) has two N-glycosylation sites (N145 and N322) and two O-glycosylation sites (S52 and S60). In transiently transfected COS-7 cells, all combinations of N- and O-glycosylation knock-out mutations reduced the release of FVII to the medium. Pulse-chase analysis of CHO-K1 cell lines expressing recombinant FVII demonstrated that virtually all wild-type FVII synthesized was secreted from the cells, whereas both N- and O- glycosylation knock-out mutations induced partial intracellular degradation of the synthesized FVII. Likewise, two thirds of the FVII synthesized in vitamin K-depleted and warfarin-treated CHO cells was degraded intracellularly, demonstrating the importance of gamma-carboxylation for the secretion of FVII. The furin inhibitor decanoyl-R-V-K-R-chloromethylketone inhibited propeptide cleavage, but FVII with propeptide appeared to be secreted equally well as FVII without propeptide. Propeptide cleavage was not inhibited by vitamin K depletion and warfarin treatment, suggesting that for FVII, correct gamma-carboxylation is not required for optimal processing of the propeptide. In conclusion, all post-translational modifications of FVII except propeptide cleavage were important for complete secretion of the synthesized FVII and to avoid intracellular degradation. Thus, the extensive post-translational modification of FVII seems critical for the intracellular stability of the protein and is required for keeping the protein in the secretory pathway.
Keywords: Factor VII; protein processing; post-translational; glycosylation; gamma-carboxylation